Parameteridentification for LTI-systems using modulating functions generated by a signal model - Schmid, Christian; Roppenecker, Günter (At-Automatisierungstechnik, 2011)
In this paper a new approach for parameter identification for linear continuous-time systems is presented which is based on the use of so called modulating functions. These modulating functions are automatically chosen such that each parameter is identifiable separately. To achieve this, a feedforward control for an especially defined time-variant signal model has to be computed, where the initial and terminal conditions for the state vector of the signal model contain the requirements for the modulating function. © Oldenbourg Wissenschaftsverlag.
Keywords: Linear continuous-time systems; Modulating functions; Parameter identification; Signal model